1996
DOI: 10.2337/diab.45.7.988
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Insulin Sensitivity and Plasma Leptin Concentration in Lean and Obese Men

Abstract: Alterations in the production of or the sensitivity to leptin, the protein encoded by the ob gene, cause obesity and diabetes in rodents. We evaluated the isolated relationship between leptin and insulin sensitivity in lean and obese humans. Three groups of subjects who were carefully matched for either insulin sensitivity (determined by the modified intravenous glucose tolerance test and minimal model analysis) or adiposity (determined by hydrodensitometry) were studied: 1) lean insulin-sensitive men (percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
176
4
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(202 citation statements)
references
References 15 publications
21
176
4
1
Order By: Relevance
“…In nondiabetic, but not in type 2 diabetic subjects a strong relationship between leptin levels and insulin action on glucose uptake in subcutaneous fat cells was also found. Previous studies have shown a relationship between in vivo insulin resistance and leptin levels [28,29], and leptin has been shown to cause insulin resistance in rat fat cells in vitro [30]. Since leptin was associated with subcutaneous fat cell size as well as insulin resistance in vitro in this study, leptin may serve as a marker and possibly be a link between fat cell size and insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…In nondiabetic, but not in type 2 diabetic subjects a strong relationship between leptin levels and insulin action on glucose uptake in subcutaneous fat cells was also found. Previous studies have shown a relationship between in vivo insulin resistance and leptin levels [28,29], and leptin has been shown to cause insulin resistance in rat fat cells in vitro [30]. Since leptin was associated with subcutaneous fat cell size as well as insulin resistance in vitro in this study, leptin may serve as a marker and possibly be a link between fat cell size and insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…In addition it has been reported that IR is associated with increased plasma leptin concentration independent of the body fat. 10 Consistent with this hypothesis, previous studies have reported that OSA is independently associated with neuroendocrine dysregulation; in fact OSA has been reported to be bRIEF SUMMARY Current knowledge/Study Rationale: Impaired glucose tolerance is a common and important co-morbidity of obstructive sleep apnea yet its pathogenesis, beyond the shared etiology of obesity is unknown. Here we tested the hypothesis that OSA might induce increases of appetite regulating hormones which might suggest a cause for IGT.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 77%
“…Because adiponectin is also directly related to body composition (25)(26), and this did not change with HRT, we would expect no change in adiponectin with HRT. Our finding of no change in adiponectin levels with HRT is consistent with a 6-month trial (45) and with a cross-sectional study (46).…”
Section: Commentmentioning
confidence: 99%
“…Leptin and adiponectin are hormones produced by fat that have been associated with amount of fat, insulin resistance, and the development of diabetes (23)(24)(25)(26). The effect of HRT on leptin is unclear, with some studies showing increases with HRT (27)(28)(29) and others finding either no change (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) or even a decrease with HRT (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%